Sociodemographic factors associated with the consumption of ultra-processed foods in Colombia - Khandpur, Neha; Cediel, Gustavo; Obando, Daniel Ayala; Jaime, Patrícia Constante; Parra, Diana C. (Revista de saúde pública, 2020)
OBJECTIVE: To analyze the consumption of ultra-processed foods in the Colombian population across sociodemographic factors. METHODS: We used data from the 2005 National Survey of the Nutritional Status in Colombia. Food consumption was assessed using a 24-hour food recall in 38,643 individuals. The food items were classified according to the degree and extent of industrial processing using the NOVA classification. RESULTS: The mean calorie contribution of ultra-processed foods ranged from 0.2% in the lowest quintile of consumers to 41.1% in the highest quintile of consumers. The greatest increases were due to the consumption of industrialized breads, sweet and savory snacks, sugary drinks, processed meats, and confectionery. No major differences were found in the consumption of ultra-processed foods between men and women. We observed significant differences by age, socioeconomic status, area of residence, and geographic region. Children and adolescents showed a higher intake of ultra-processed foods, almost double that of participants over 50 years of age. Children consumed significantly more snacks, confectionery products, processed cereals, milk-based drinks and desserts. Participants over 50 years consumed fewer products from these sub-groups of ultra-processed foods but had the highest consumption of industrialized bread. Individuals from urban areas, those with high socioeconomic status, participants residing in the Bogotá region had 1.5 to 1.7 times higher calorie intake from ultra-processed foods compared with those from a lower socioeconomic status and those residing in rural regions. CONCLUSION: In Colombia, industrialized bread is the ultra-processed product that is most easily assimilated into the traditional diet, along with snacks and sugary drinks. Children and adolescents residing in urban areas and households with greater purchasing power have some of the highest intakes of ultra-processed foods in the country.